Implementation of Pancasila Student Profile Values Through Traditional Kawsilo (Cloth) Games at Tiwi Kindergarten – Emplawas - Jeditia Taliak (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this research is to look at how traditional Kawsilo games, which incorporate Pancasila student profile principles, affect the students' personalities. A classroom action research strategy is utilized in the investigation. For this study, we used documentation, interviews, and observation to gather data. In this investigation, we use a method of data analysis that falls into two broad classes: quantitative and qualitative. Children at Tiwi Kindergarten did not show a notable improvement in their Pancasila student profile after playing the Kawsilo game during Cycle I's first two meetings. While the Pancasila student profile was still classified as less good or active, it improved from 57.14% in Cycle I, the first meeting, to 64.28% in Cycle II, the second meeting. As a result, more testing must be done for Cycle II. We held two meetings to continue the action in Cycle II. The pupils' Pancasila student profile significantly improved, according to the observation data. The percentage value in Cycle II clearly demonstrates the increase, with the first meeting reaching 77.22% and the second meeting reaching 80.45%, both of which fall into the good/active category. The concept of "Merdeka Belajar" creates an active, free, and stimulating learning environment for students and teachers, allowing students to choose their learning resources without pressure. The Pancasila student profile serves as the cornerstone of the independent curriculum, with the goal of molding students' personalities and abilities. Our school's culture, curriculum, and extracurricular and co-curricular activities all contribute to its implementation.